Designing Regulatory Frameworks for Access to Genetic Resources: A Multi-Stakeholder Multi-Criteria Approach - Sirakaya, Aysegul; De Brucker, Klaas; Vanagt, Thomas (Frontiers in Genetics, 2020)
In this paper we conduct a multi-criteria analysis (MCA) from a multi-stakeholder point of view for the design of “access and benefit sharing” (ABS) agreements in the realm of genetic resources. We focus especially on the access component of such agreements. We start by analysing the objectives defined by international law (i.e. the Convention on Biodiversity and the Nagoya Protocol) that every signatory (i.e. all United Nations member states, except the United States) must strive to attain when developing national legislation on ABS. Individual countries do have discretion as to how and to what extent they want to pursue these objectives through their national policy frameworks. In addition, different stakeholders attach varying levels of importance to these objectives. Our MCA helps identifying those options that are likely to lead to the highest value added from the vantage point of the community of stakeholders. Consequently, those options are expected to hold the highest potential for successful implementation. The MCA performed in this paper is based on Saaty’s analytic hierarchy process (AHP). It starts from the objectives (i.e. criteria) enshrined in international law, and then assesses the relative importance of these criteria from the point of view of four different stakeholder groups (industrial users, academic users, collections and provider countries). The various policy options we assess in the MCA were identified in an earlier study published in Frontiers in Plant Science. In the present paper, we consider these options to be ‘design parameters’. We evaluate these options in terms of their contribution to criteria viewed as important by stakeholders. Our quantitative MCA evaluation builds upon qualitative information from stakeholders. The MCA identifies which design parameters in the realm of access are given the highest priority by the community of stakeholders, and hence should be present in national regulatory frameworks on ABS that will be implemented by member states.